Surface Deterioration of Indirect Restorative Materials - Mushashe,Amanda Mahammad (2020)
Abstract The objective of this work was to evaluate the effects of in vitro and in situ biodegradation on the surface characteristics of two resin cements and a hybrid ceramic system. One hundred and eighty specimens (4X1.5mm) of each material (Maxcem Elite, NX3 Nexus and Vita Enamic) were made and randomly distributed in twelve groups (n=15) according to the material and biodegradation method. The specimens were then submitted to the following challenges: storage in distilled water 37 ºC for 24 h or 7 days, storage for 7 days, at 37 ºC, in stimulated saliva or in situ. The in situ stage corresponded to the preparation of 15 intraoral palatal devices, used for 7 days. Each device presented 3 niches, where a sample of each materials was accommodated. Specimens from both saliva and in situ groups suffered a cariogenic challenge, corresponding to the application of a solution of 20% of sucrose, 10 times throughout each day. After each biodegradation method, the surface roughness (Ra), Vickers hardness (VHN) and scanning electron microscopy (SEM) analyzes were performed. The data collected were evaluated by Levene test, two-way ANOVA and Tukey`s test (α=5%). The in situ challenge promoted the greater biodegradation, regardless of the material. Regarding the materials, the Vita Enamic VHN was negatively affected by all biodegradation methods and the Nexus NX3 presented better performance than the self-adhesive cement tested. Therefore, within the conditions of this work, it was concluded that in situ biodegradation can affect negatively the surface characteristics of indirect restorative materials.